Two-phase extraction culture of Botryococcus braunii producing long-chain unsaturated hydrocarbons - Sim, SJ; An, JY; Kim, BW (KLUWER ACADEMIC PUBL, 2001)
Hydrocarbon recovery was 32% and the total production of hydrocarbon in a two-phase extraction culture of Botryococcus braunii was 675 mg l(-1), which was 19% higher than that of single-phase culture. Addition of 60 ml dihexyl ether at mid-growth phase gave the highest yield. Specific growth rate and recovery of hydrocarbon in this case were 0.022 h(-1) and 26%, respectively.
Keywords: RECOVERY; GROWTH; STRAIN